STRATEGIES FOR IMPROVING TECHNICAL AND VOCATIONAL EDUCATION (TVE) PROGRAMME TO REDUCE UMEMPLOYMENT IN NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
Technical and Vocational Education (TVE) is geared towards the development ofspecific skills for economic and social challenges. Considering the high rate ofunemployment of TVE Nigerian graduates especially the secondary school leaversand the university graduates, it becomes pertinent to critically examine the role ofTVE and proffer strategies for its improvement towards ameliorating the situation.This study therefore ascertains the state of TVE in Nigeria, emerging challenges inTVE and proposed strategies towards enhancing the TVE programme in Nigeria foreconomic development. The study would be of benefit to the researchers andcurriculum planners as it would contribute to literature and enhance the knowledgeof the curriculum planners on the strategies to include when planning thecurriculum to improve TVE programme in order to reduce the rate of unemploymentand poverty in Nigeria.
Keywords: Economic development, Employment generation, Poverty reduction, Technical and Vocational Education (TVE).